1998
DOI: 10.1152/ajpcell.1998.274.1.c25
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive K+ channels in pancreatic, cardiac, and vascular smooth muscle cells

Abstract: ATP-sensitive K+(KATP) channels are therapeutic targets for several diseases, including angina, hypertension, and diabetes. This is because stimulation of KATP channels is thought to produce vasorelaxation and myocardial protection against ischemia, whereas inhibition facilitates insulin secretion. It is well known that native KATP channels are inhibited by ATP and sulfonylurea (SU) compounds and stimulated by nucleotide diphosphates and K+channel-opening drugs (KCOs). Although these characteristics can be sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
254
1
25

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(289 citation statements)
references
References 146 publications
9
254
1
25
Order By: Relevance
“…Because these channels are regulated by the levels of ATP, they provide an important link between cellular metabolism and excitability (Kakei et al 1985;Kakei et al 1986;Ashcroft 1988;Ashcroft and Kakei 1989). In this regard, K ATP channels control the release of insulin from pancreatic β cells (Ashcroft et al 1984;Ashcroft and Gribble 1998;Miki et al 1999;Schwanstecher et al 1998;Seino 1999) and blood flow in muscle, heart, and kidney tissue (Ashcroft 1988;Nelson and Quayle 1995;Terzic et al 1995;Yokoshiki et al 1998). In neurons, activation of K ATP results in membrane hyperpolarization that reduces excitability (Yamada et al 2001;Allen and Brown 2004) and activation of presynaptic K ATP channels can directly modulate neurotransmitter release from nerve terminals (Deist et al 1992;Ohno-Shosaku et al 1992;Watts et al 1995;Ye et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Because these channels are regulated by the levels of ATP, they provide an important link between cellular metabolism and excitability (Kakei et al 1985;Kakei et al 1986;Ashcroft 1988;Ashcroft and Kakei 1989). In this regard, K ATP channels control the release of insulin from pancreatic β cells (Ashcroft et al 1984;Ashcroft and Gribble 1998;Miki et al 1999;Schwanstecher et al 1998;Seino 1999) and blood flow in muscle, heart, and kidney tissue (Ashcroft 1988;Nelson and Quayle 1995;Terzic et al 1995;Yokoshiki et al 1998). In neurons, activation of K ATP results in membrane hyperpolarization that reduces excitability (Yamada et al 2001;Allen and Brown 2004) and activation of presynaptic K ATP channels can directly modulate neurotransmitter release from nerve terminals (Deist et al 1992;Ohno-Shosaku et al 1992;Watts et al 1995;Ye et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1 Although these channels would normally be closed in cardiac myocytes, during myocardial ischemia, where the cellular ATP:ADP ratio falls substantially, activation of K ATP channels could contribute to cardioprotective mechanisms. 2,3 Functional K ATP channel currents have been demonstrated in both cardiac sarcolemmal 4 (sarcK ATP ) and mitochondrial (mitoK ATP ) membranes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…7 The pharmacological properties of channels expressed in heterologous systems suggest strongly that the sarcK ATP channel is composed of Kir6.2 and SUR2A subunits. 1 Current flow via Kir6.2 subunits in sarcK ATP channels is integral to mechanisms of action potential shortening. This was shown by the rescue of pinacidilinduced outward current and action potential shortening in ventricular cells from Kir6.2 -/-knockout mice by gene transfer of the Kir6.2 subunit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine 5 0 -triphosphate-sensitive potassium (K ATP ) channels are widely distributed in a variety of tissue and cell types, where they couple intracellular metabolic changes to the electrical activity of the plasma membrane, thus playing an important role in both physiology and pathology. Electrophysiological studies have shown that the kinetics and pharmacological properties of K ATP channels vary among different tissues, 1 suggesting structurally and functionally distinct types.…”
Section: Introductionmentioning
confidence: 99%